2008
DOI: 10.1163/157181808x311222
|View full text |Cite
|
Sign up to set email alerts
|

Foucault, Power and Participation

Abstract: In this paper, I argue that Foucault's work on power off ers a distinctive and original perspective with the potential to aff ord insights into the nature of participation. I begin by providing a brief exegesis of Foucault's conceptualisation of power in his middle to late work. Th e notion of governmentality is drawn out as a potentially useful tool in understanding participation as a profoundly ambiguous phenomenon. I conclude by outlining some of the possible implications of Foucault's thinking about power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
118
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 15 publications
3
118
0
9
Order By: Relevance
“…They presented these to workers who changed their practice without a change in policy. When participation is to have a product which is external change, this confirms Mannion's (2007) and Gallagher's (2008) argument for moving away from participation primarily focused on influencing governments and concentrating instead on local contexts with their social, cultural and historical aspects (Cornwall & Coelho, 2007). In other instances, products sought may be changes in policy, guidance or distribution of resources; this may require a national focus.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…They presented these to workers who changed their practice without a change in policy. When participation is to have a product which is external change, this confirms Mannion's (2007) and Gallagher's (2008) argument for moving away from participation primarily focused on influencing governments and concentrating instead on local contexts with their social, cultural and historical aspects (Cornwall & Coelho, 2007). In other instances, products sought may be changes in policy, guidance or distribution of resources; this may require a national focus.…”
Section: Discussionsupporting
confidence: 54%
“…Confirming that participation is messy (Gallagher, 2008), fluid (Horwath, Kalyva, & Spyru, 2012) and relational (Mannion, 2007) these case studies also revealed how resources could be mobilised by different actors (young people in core groups -Auditors, Child Researchers, Survivors and Developers; other young participants; adult facilitators; other workers; managers and decision makers; and ombudsmen) through practices such as suggesting, deciding and dialogue. Dialogue was a circular process through which different actors suggested, responded, decided and then acted in accordance with shared decisions.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Segundo ele, um processo educativo voltado para isso é primordial para que as crianças consigam usufruir dessas possibilidades. Gallagher (2008) avança na crítica ao possível aumento da participação das crianças nas relações travadas na internet. Segundo seu estudo, há duas correntes que avaliam, de maneira oposta, o aumento da participação (das falas) das crianças no jogo social: a otimista, que acredita que esse crescimento seria "uma maneira de transformar injustas estruturas de decisão para que a voz de cada criança possa ser ouvida e seus desejos, atendidos 3 "; e a pessimista, que entende que "a participação é muitas vezes não efetiva, com adultos consultando crianças, mas não agindo de acordo com as suas sugestões para a mudança 4 " (GALLAGHER, 2008, p. 404, tradução nossa).…”
unclassified
“…Acrescentamos ao pensamento de Gallagher (2008) Todas essas mensagens foram analisadas segundo uma grade analítica:…”
unclassified